Gestión pública y su influencia en los procesos institucionales de los docentes de la Unidad Educativa Puebloviejo - Macias Monar, Karen Cecilia (2021)
This case study was developed with the purpose of verifying the management of public management and institutional processes in the teachers of the “Puebloviejo” Educational Unit, in which the institution is located in the Puebloviejo canton, Los Ríos province, since public management is very fundamental in the institution because it allows a better organization, together with the institutional processes which are fundamental in every institution so that they have good planning both in the administrative and academic areas, because in this way we can promote institutional and student well-being . To verify this research, the virtual survey was carried out on the google forms platform, which were carried out to teachers, with the purpose of achieving changes in a public institution, so that it is organized, with essential principles and parameters to be able to achieve the objectives desired, through the survey that the teachers gave us, we can see the representation of obtaining a better solution, since this issue of public management and institutional processes is of great importance in the teachers and administrators of said institution. It was possible to show that this case study is very feasible because it facilitates public management to understand its challenges in both teachers and students because in this era of globalization and technology, appropriate tools are required for the use of electronic media and social networks so that they can function in the modern environment and have more knowledge about what public management and institutional processes are.